## Active forum topics

- General Solution of $y' = x \, \ln x$
- engineering economics: construct the cash flow diagram
- Eliminate the Arbitrary Constants
- Law of cosines
- Maxima and minima (trapezoidal gutter)
- Special products and factoring
- Integration of 4x^2/csc^3x√sinxcosx dx
- application of minima and maxima
- Sight Distance of Vertical Parabolic Curve
- Application of Differential Equation: Newton's Law of Cooling

## New forum topics

- General Solution of $y' = x \, \ln x$
- engineering economics: construct the cash flow diagram
- Integration of 4x^2/csc^3x√sinxcosx dx
- Maxima and minima (trapezoidal gutter)
- Special products and factoring
- Newton's Law of Cooling
- Law of cosines
- Can you help me po to solve this?
- Eliminate the Arbitrary Constants
- Required diameter of solid shaft

## Recent comments

- 400000=120[14π(D2−10000)]

(…1 week 6 days ago - Use integration by parts for…1 month 1 week ago
- need answer1 month 1 week ago
- Yes you are absolutely right…1 month 2 weeks ago
- I think what is ask is the…1 month 2 weeks ago
- $\cos \theta = \dfrac{2}{…1 month 2 weeks ago
- Why did you use (1/SQ root 5…1 month 2 weeks ago
- How did you get the 300 000pi1 month 2 weeks ago
- It is not necessary to…1 month 2 weeks ago
- Draw a horizontal time line…1 month 2 weeks ago

## Re: find the equation of a circle passing through (-1,6) and...

Let

_{1}= distance between (h, k) and (-1, 6)_{2}= distance between (h, k) and x - 2y + 8 = 0_{3}= distance between (h, k) and 2x + y + 6 = 0_{1}= r_{2}= r_{3}$r_1 = \sqrt{(h + 1)^2 + (k - 6)^2}$

$r_2 = \dfrac{h - 2k + 8}{(-)(+)\sqrt{1^2 + (-2)^2}} = \dfrac{h - 2k + 8}{-\sqrt{5}}$

$r_3 = \dfrac{2h + k + 6}{(+)(+)\sqrt{2^2 + 1^2}} = \dfrac{2h + k + 6}{\sqrt{5}}$

$r_2 = r_3$

$\dfrac{h - 2k + 8}{-\sqrt{5}} = \dfrac{2h + k + 6}{\sqrt{5}}$

$-h + 2k - 8 = 2h + k + 6$

$k = 3h + 14$

$r_1 = r_3$

${r_1}^2 = {r_3}^2$

$(h + 1)^2 + (k - 6)^2 = \dfrac{(2h + k + 6)^2}{5}$

Substitute k = 3h + 14

$(h + 1)^2 + (3h + 14 - 6)^2 = \dfrac{(2h + 3h + 14 + 6)^2}{5}$

$(h + 1)^2 + (3h + 8)^2 = \dfrac{(5h + 20)^2}{5}$

$(h^2 + 2h + 1) + (9h^2 + 48h + 64)^2 = \dfrac{25h^2 + 200h + 400}{5}$

$10h^2 + 50h + 65 = 5h^2 + 40h + 80$

$5h^2 + 10h - 15 = 0$

$h^2 + 2h - 3 = 0$

$(h - 1)(h + 3) = 0$

$h = 1 ~ \text{and} ~ -3$

When h = 1

$r^2 = (1 + 1)^2 + (17 - 6)^2$

$(x - 1)^2 + (y - 17)^2 = 125$

answerWhen h = -3

$r^2 = (-3 + 1)^2 + (5 - 6)^2$

$(x + 3)^2 + (y - 5)^2 = 5$

answer## Re: find the equation of a circle passing through (-1,6) and...

Realize the two lines are perpendicular.

Intersection of the lines, by isolating and equating y:

x/2+4=-2x-6

(-4,2)

By trig, find slope of bisector of the two lines is 3.

Equation of bisector in point-slope form is 3=(y-2)/(x+4) => k=3h+14 {1}

Distance from center of circle to (-4,2) is sqrt(2)*Distance from center of circle to (-1,6)

(h+4)

^{2}+(k-2)^{2}=2*((h+1)^{2}+(k-6)^{2})Simplify and sub in {1}

0=h

^{2}+2h-3h=-3 or 1, k=5 or 17, r

^{2}=25 or 125 by back substitutionIt's about the same length and complexity as the previous answer